Soap Made from Kesum Leaf Squeezedto Inhibit Growth Staphylococcus aureus. - Bagus Muhammad Ihsan; Elisabeth Lusitania; Sugito (POLTEKKES KEMENKES PONTIANAK, 2023)
Biodiversity, especially in West Kalimantan, is very diverse, one of which is the kesum plant (Polygonum minus husks). The kesum plant is a plant that can be used as herbal medicine. The utilization of kesum plants is usually done as part of the leaves, namely as local processed cooking spices. Based on Fitofarmaka studies, kesum plants are believed to have antibacterial, antifungal, anti-viral, antioxidant, anti-cancer, and antiulcer activities. The study's aim was to find out how well different concentrations of kesum leaf juice-based solid soap formulations stopped the growth of Staphylococcus aureus bacteria. This study used kesum leaves (Polygonum minus husks), which were squeezed, and then made solid soap preparations with concentrations of 3.93%, 5.25%, and 6.56%. Nine repetitions were carried out in each treatment, so the number of samples used was 27. The results of the antibacterial inhibition test showed that the soap preparation samples had the ability to inhibit the growth of Staphylococcus aureus bacteria. The result of the statistical analysis value in the Friedman test is P = 0.000, which states that there is a difference in each concentration of solid soap prepared from kesum leaf juice. Dilution concentrations of 5.25% and 6.56% are more effective in inhibiting the growth of Staphylococcus aureus bacteria than 3.93%.